“Wordwall Open the Box” : Cara Inovatif Mengajar Anak Usia Dini - Surya, Surya; Usman, Usman; Nurhidayah Ilyas, Sitti; Rahayu, Rahayu; Safitri, Nuralia (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
This research aims to evaluate the effectiveness and benefits of Wordwall's Open the Box method in early childhood education. The main contribution of this research is to prove how this innovative method can increase students' participation and understanding, stimulate the development of cognitive and motor skills, and utilize technology in effective education and personalized learning. The Open the Box method is an interactive learning concept that utilizes digital technology in the teaching and learning process. In this study, we used a qualitative research design by conducting in-depth interviews with teachers who have implemented this method in their teaching. The results show that Open the Box method can increase children's participation and enthusiasm in learning, help them understand concepts better, stimulate the development of cognitive and motor skills, and show how technology can be used effectively in early childhood education. In addition, Wordwall allows personalization of learning according to each child's needs and skill level. However, this study has some limitations, such as the limited number of respondents and only focusing on one teaching method. Therefore, further research is needed to verify and extend the findings of this study, as well as explore the potential of other methods and technologies in early childhood education.